Complementary therapies for clinical depression: an overview of systematic reviews - Heidemarie Haller; Dennis Anheyer; Holger Cramer; Gustav Dobos (BMJ Open)
Objectives As clinical practice guidelines vary widely in their search strategies and recommendations of complementary and alternative medicine (CAM) for depression, this overview aimed at systematically summarising the level 1 evidence on CAM for patients with a clinical diagnosis of depression.Methods PubMed, PsycInfo and Central were searched for meta-analyses of randomised controlled clinical trials (RCTs) until 30 June 2018. Outcomes included depression severity, response, remission, relapse and adverse events. The quality of evidence was assessed according to Grades of Recommendation, Assessment, Development, and Evaluation (GRADE) considering the methodological quality of the RCTs and meta-analyses, inconsistency, indirectness, imprecision of the evidence and the potential risk of publication bias.Results The literature search revealed 26 meta-analyses conducted between 2002 and 2018 on 1–49 RCTs in major, minor and seasonal depression. In patients with mild to moderate major depression, moderate quality evidence suggested the efficacy of St. John’s wort towards placebo and its comparative effectiveness towards standard antidepressants for the treatment for depression severity and response rates, while St. John’s wort caused significant less adverse events. In patients with recurrent major depression, moderate quality evidence showed that mindfulness-based cognitive therapy was superior to standard antidepressant drug treatment for the prevention of depression relapse. Other CAM evidence was considered as having low or very low quality.Conclusions The effects of all but two CAM treatments found in studies on clinical depressed patients based on low to very low quality of evidence. The evidence has to be downgraded mostly due to avoidable methodological flaws of both the original RCTs and meta-analyses not following the Consolidated Standards of Reporting Trials and Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Further research is needed.